The Carotid Body a Common Denominator for Cardiovascular and Metabolic Dysfunction? - Badoer, Emilio (Frontiers in Physiology, 2020)
The carotid body is a highly vascularised organ designed to monitor oxygen levels. Reducing oxygen levels in blood results in increased activity of the carotid body cells and reflex increases in sympathetic nerve activity. A key contributor to elevated sympathetic nerve activity in neurogenic forms of hypertension is enhanced peripheral chemoreceptor activity. Hypertension commonly occurs in metabolic disorders, like obesity. Such metabolic diseases are serious global health problems. Yet, the mechanisms contributing to increased sympathetic nerve activity and hypertension in obesity are not fully understood and a better understanding is urgently required. In this review, we examine the literature that suggests that overactivity of the carotid body may also contribute to metabolic disturbances. The purine ATP is an important chemical mediator influencing the activity of the carotid body and the role of purines in the overactivity of the carotid body is explored. We will conclude with the suggestion that tonic overactivity of the carotid body may be a common denominator that contributes to the hypertension and metabolic dysfunction seen in conditions in which metabolic disease exists such as obesity or insulin resistance induced by high caloric intake. Therapeutic treatment targeting the carotid bodies may be a viable treatment since translation to the clinic could be more easily performed than expected via repurposing antagonists of purinergic receptors currently in clinical practice, and the use of other minimally invasive techniques that reduce the overactivity of the carotid bodies which may be developed for such clinical use.